MODULATED MOLECULAR-BEAM MASS-SPECTROMETRY STUDIES OF THE GROWTH OF GAAS AND INXGA1-XAS USING TRI-ISOBUTYLGALLIUM - Levoguer, C; Foord, J; Davies, G; Skevington, P (Elsevier, 1994)
Modulated molecular beam mass spectroscopy (MBMS) studies of the CBE growth of GaAs and InxGa1-xAs using tri-isobutylgallium (TiBG) have been carried out. The results show similarities to studies which have been carried out previously using triethylgallium (TEG) in that hey indicate that the GRa deposition efficiency is controlled by a temperature-dependent probability for the desorption of alkyls from the growth surface. Differing decomposition temperatures, desorbing species and effects arising when trimethylindium (TMI) is introduced to the growth system, are observed, however, for TiBG. The origins of these key differences are discussed.